POMD11 Cannabinoids are neuroprotective in a human cell culture model of Parkinson's disease. Issue 11 (22nd October 2010) - Carroll, C; Zajicek, J P; Hanemann, C O; Stone, V; Zeissler, M
Abstract : Background: We have previously shown a protective effect of Δ9-tetrahydrocannabinol (THC) in Parkinson's disease (PD) cell culture models associated with increased CB1 cannabis receptor cDNA. Here we investigate whether this protective effect is mediated via the CB1 receptor. Methods: SH-SY5Y human neuroblastoma cells were differentiated to a neuronal phenotype. The presence of an endocannabinoid system (ECS) was investigated by immunocytochemistry, Western blotting and reverse transcriptase PCR. Cannabinoids and ECS modulators were co-administered with PD-relevant toxins (MPP+ (mitochondrial inhibitor), lactacystin (proteasome inhibitor), paraquat (free radical generator) to determine any protective effect. Results: The protective effect of Δ9-THC was not blocked by the CB1 antagonist AM251, nor reproduced by the CB1 agonist WIN55, 212-2. Δ9-THC is known to be antioxidant. Cannabidiol, an antioxidant with little CB1 receptor affinity, exerted a protective effect against MPP+ with no effect against paraquat or lactacystin. Cannabidiol may be acting via modulation of anandamide hydrolysis. We found expression of the enzyme involved in endocannabinoid hydrolysis, fatty-acid amide hydrolase (FAAH). Co-administration of URB597, an FAAH inhibitor, was protective against MPP+, an effect which was not blocked by antagonism of the CB1 receptor. Conclusions: Our results suggest that the protective effects of cannabinoids in cell culture models of PD may be mediated by modulation of the ECS.